Scolding the child who threw the scissors: Shaping discourse expectations by restricting referents. Issue 3 (2nd April 2021) - Hoek, Jet; Rohde, Hannah; Evers-Vermeul, Jacqueline; Sanders, Ted J. M.
ABSTRACT: Coherence relations are often assumed to hold between clauses, but restrictive relative clauses (RCs) are usually not granted discourse segment status because they are syntactically and conceptually integrated in their matrix clauses. This paper investigates whether coherence relations can be inferred between restrictive RCs and their matrix clauses. Three experiments provide converging evidence that restrictive RCs can indeed play a role at the discourse level and should not categorically be excluded from receiving discourse segment status in discourse annotation practices. At the same time, the studies provide new insights into implicit causality verb biases, specifically about next-mention biases in concessive coherence relations, and expectations about discourse structure, upcoming referents, and upcoming coherence relations.